The Impact of Leadership Traits in Developing Organizational Citizenship Behavior - A Practical Study on The Staff of The General Authority of Meteorology and Environmental Protection in Jeddah Province- - Alamri, Sultan Ahmed; Taibah, Hassan Abdulqadir (Journal of Economic, Administrative and Legal Sciences, 2021)
This study came with several objectives, most notably to discuss the impact of leadership features in the development of organizational citizenship behavior, from the point of view of employees in The General Authority of Meteorology and Environmental Protection in Jeddah Province. To achieve the objectives of the study, the researcher followed the descriptive analytical method, to conduct this study, in addition to using the questionnaire as a main tool to collect data from the study sample individuals. The study population consisted of 800 employees in The General Authority of Meteorology and Environmental Protection in Jeddah Province. A simple random sample of 260 employees from The General Authority of Meteorology and Environmental Protection in Jeddah Province. The study reached several important results, the most important of which were: There is a statistically significant effect at the level (α ≤ 0.05) of the traits (social- behavioral- personal- professional) of the leader individually, on developing organizational citizenship behavior in its various dimensions (Altruism, graces and sweetness, living conscience) of staff of the General Authority of Meteorology and Environmental Protection in Jeddah Province, Where the coefficient of multiple correlation between the axis of leadership Traits in its different dimensions, and the axis of organizational citizenship behavior in its various dimensions 0.718. In light of the results of the study, the study reached several recommendations as follows: Increased interest in studying the results of the impact of leadership traits in developing organizational citizenship behavior In its various dimensions of staff of the General Authority of Meteorology and Environmental Protection in Jeddah Province, and evaluated in order to allow the field to improve the career work within the authority, and these are a positive effect in reducing the rates of occupational leakage.